Unboxing the Role of E-Commerce Ecosystems to Address Grand Challenges - Wulfert, Tobias; Woroch, Robert; Strobel, Gero; Schoormann, Thorsten; Banh, Leonardo (ECIS 2023 Research Papers, 2023)
The modern world is confronted with grand challenges, such as those codified by the United Nations’ Sustainable Development Goals. As single organizations are often not capable of addressing a broad set of goals on their own, they are increasingly concerned with creating ecosystems. This is also the case in the domain of e-commerce. Owners of focal platforms in e-commerce ecosystems have the power to implement sustainability initiatives and therefore need to be equipped with an overview of possible initiatives and actionable guidance. To unbox how e-commerce ecosystem participants consider sustainability, we conducted a multi-case study with 99 initiatives collected from sustainability reports. We found that (1) sustainability initiatives particularly focus on reducing inequality and managing climate change as well as (2) manufacturers, sellers, and service providers are the most involved ecosystem participants. Based on our findings, we (3) synthesized six categories of sustainability initiatives as measurements.